Phylogeny and evolutionary genetics of porcine parvovirus in wild boars - Cadar, Dániel; Dán, Ádám; Tombácz, Kata; Lőrincz, Márta; Kiss, Timea; Becskei, Zsolt; Spînu, Marina; Tuboly, Tamás; Cságola, Attila (Infection, genetics and evolution, 2012)
► Genetic diversity and evolution of porcine parvovirus in wild boars were studied. ► PPVs of wild boars proved to be more diverse than viruses of domestic pigs. ► High rate of evolution for VP1/VP2 genes was found. ► PPV has a relatively recent evolutionary history, diverged in the last 20–60years. Porcine parvovirus (PPV) is widespread among swine and is responsible for reproductive failure of susceptible sows, characterized by embryonic and fetal death. Studies showed that PPV in domestic pig is genetically diverse and some strains differ from the ones used for vaccination. Organ samples from wild boars and domestic pigs were collected in Transylvania (Romania) and tested for the presence of PPV by polymerase chain reaction. Positive samples were grouped and 14 from the wild boar and 1 from the domestic pig PPVs were selected for VP1/VP2 sequence analysis and comparison with available GenBank data. The molecular clock analysis revealed that PPV has a relatively recent evolutionary history, originated approximately 120years ago and the main divergence occurred in the last 20–60years. Phylogenetic and residue substitution analysis showed that the viruses could be divided into 6 distinct clusters and that wild boar PPVs were partially different and independent from domestic pig PPVs. PPVs of wild boars proved to be more diverse than viruses of domestic pigs. The presence of the highly virulent 27a-like PPV strains in wild boars was also detected.